Manufacturing Industry Performance Appraisals: Multi-Criteria Decision-Making Model - Andriani, Debrina Puspita; Wijayanti, Febry; Rahmani, Ilma Visi; Aini, Azizah Putri Nur (International Journal of Integrated Engineering, 2022)
Companies with assessment criteria often consider only the leader’s subjectivity and ignore other criteria. Limited appraisal criteria result in shortcomings in the decision-making process. This study examines the performance appraisal in a plastic manufacturing company’s production floor and develops a multi-criteria decision-making model for performance appraisal by considering company criteria. We propose a qualitative approach using the analytic network process to determine the weighted criteria and sub-criteria to evaluate performance by involving all criteria. The results show that qualitative performance criteria yield higher scores for workers than the quantitative performance criteria, thereby confirming that subjectivity and qualitative criteria influence performance appraisal in the manufacturing industry. A multi-criteria decision-making model is required in performance appraisals to determine the overall measurable criteria. Moreover, this study contributes to an empirical solution for achieving an effective human resource management system.